PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SMART APPS CREATOR (SAC) TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI 1 ENREKANG - Suhardi, Mujahidah; Pagarra, Hamzah; Prima Findiga Hermuttaqien, Bhakti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using interactive learning media based on Smart Apps Creator (SAC) on the learning interest of fifth-grade students at SD Negeri 1 Enrekang. This study was based on initial observations indicating that students dislike mathematics lessons due to the abstract concepts often considered difficult to understand, as well as the uninteresting presentation of material using conventional learning methods, indicating low learning interest. Using a quantitative approach with a quasi-experimental nonequivalent control group design, this study involved all fifth-grade students at SD Negeri 1 Enrekang. The study sample consisted of 25 students from class VA as the control class and 25 students from class VB as the experimental class, selected using a purposive sampling technique. Data collection was conducted using a learning interest questionnaire and an observation sheet on the implementation of the SAC media. Data analysis was conducted descriptively and inferentially. The results showed that (1) The implementation of the SAC media in the experimental class was very successful, with a significant increase in observations from “good” to “very good”. (2) The learning interest of students in the experimental class was significantly higher than that of the control class, as evidenced by posttest scores showing a greater number of students in the very high category in the experimental class. (3) There was a positive and significant effect of the use of SAC media on student learning interest, with a probability value of less than 0.05, indicating a clear difference between classes using SAC media and those not. This study concludes that interactive learning media based on Smart Apps Creator is effective in increasing student learning interest in Mathematics.